Public health as a community interest: what role for the European Court of Human Rights - Seibert-Fohr, Anja (German yearbook of international law, 2022)
The article considers the increasing role of public health issues in individual complaints brought before the European Court of Human Rights. On the basis of the Court’s recent jurisprudence, it shows how the Court allows necessary measures to protect public health as a relevant aspect of human rights protection without giving States ‘carte blanche’ to restrict excessively individual freedoms and liberty. On a more general level, the contribution evaluates to what extent proceedings before the Court can contribute to the protection of this important community interest. Using the example of public health, it seeks to respond to questions raised by Rüdiger Wolfrum in this volume about the role of international dispute settlement mechanisms for the defense of community interests.
Gesehen am 03.05.2024
Keywords: Impfung; Pandemie; COVID-19; Europäischer Gerichtshof für Menschenrechte; Menschenrecht; Public Health